Establishment of rapid risk assessment model for cigarette smoke extract exposure in chronic obstructive pulmonary disease. (November 2019) - Chen, Xuemei; Li, Yuping; Hua, Chenfeng; Jia, Peijun; Xing, Yinpei; xue, Bohan; Tian, Xiaoyi; Yang, Yuanyuan; Zhang, Junxia; Qiao, Liangjun; Liu, Huimin; Li, Xiang; et al.
Abstract: Rapid risk assessment models for different types of cigarette smoke extract (CSE) exposure are critical to understanding the etiology of chronic obstructive pulmonary disease. The present study investigated inflammation of cultured tracheal tissues with CSE exposure. Rat trachea rings were isolated, cultured, then exposed to various concentrations of CSE from 3R4 F reference cigarettes for 4 h. Tissue/cellular morphology, ultrastructure, viability and damage, inflammatory cell infiltration, and inflammatory protein levels were measured and compared to untreated controls. Human bronchial epithelial cells (BEAS-2B) exposed to 0 or 300 μg/mL CSE were cocultured with macrophages to assess extent of mobilization and phagocytosis. Endotracheal epithelium cilia densities were significantly reduced with increasing CSE concentrations, while mucous membranes became increasingly disordered; both eventually disappeared. Macrophages became larger as the CSE concentration increased, with microvilli and extended pseudopodium covering their surface, and many primary and secondary lysosomes present in the cytoplasm. Inflammatory cell infiltration also increased with increasing CSE dose, as did intracellular adhesion molecule-1(ICAM-1), interleukin-6(IL-6). The method described here may be useful to qualitatively characterized the effects of the compound under study. Then, we use BEAS-2B cell line system to strength the observation made in the cultured tissues. Probably, an approach to integrate results from both experiments will facilitate its application. These results demonstrate that cultured rat tracheal rings have a whole-tissue structure that undergoes inflammatory processes similar to in vivo tissues upon CSE exposure.